(3TQM GdSeGY GdWHjYis - (3GHf SfGs
(3ChdgG (B:s
(3bGd CQSWhWGdjS deG cGfJ MGd GdYde hGdjbjf ai LejY GdSHd s
(3BNQgG (B:s
(3hbO Jcde Ydjg ajeG bHd hbjd dh cGfJ MQcI Gdadc deG cGfJ GdMQcI hGMOI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3djOf (B(583) s
Keywords: (3GdadSaI hGdefWbs